2006
DOI: 10.2214/ajr.04.1619
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Wall Endometriosis: Clinical Presentation and Imaging Features with Emphasis on Sonography

Abstract: Abdominal wall endometriosis frequently presents with noncyclic symptoms. Imaging findings of a solid mass near a cesarean section scar strongly suggest its diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
179
0
15

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(199 citation statements)
references
References 13 publications
5
179
0
15
Order By: Relevance
“…It occurs in up to 15% of women in the reproductive age group (age range 15-57 years) [2]. This ectopic endometrial tissue is mostly detected intra or extrapelvic and it rarely involves the abdominal wall.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It occurs in up to 15% of women in the reproductive age group (age range 15-57 years) [2]. This ectopic endometrial tissue is mostly detected intra or extrapelvic and it rarely involves the abdominal wall.…”
Section: Discussionmentioning
confidence: 99%
“…This ectopic endometrial tissue is mostly detected intra or extrapelvic and it rarely involves the abdominal wall. When the abdominal wall is affected, the visceral peritoneum layer is the most commonly affected [2]. The AWE is a rare occurrence that some authors have reported incidences between 0,03-3,5% [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the transport theory, endometrial cells are transported to extrauterine areas in some instances and endometrioma develops by being affected by hormonal changes. 5 Another hypothesis suggests the presence of diminished natural killer cell immunity, which lessens the clearance of endometrial cells from peritoneum. 6 Endometrioma developing in CS scar tissue can be explained on the basis of theory of transportation.…”
Section: Discussionmentioning
confidence: 99%